2005
DOI: 10.33899/rden.2005.45486
|View full text |Cite
|
Sign up to set email alerts
|

The effects of type of tooth and the placement site of electrode on the electrical pulp testing of the anterior teeth

Abstract: The aim of this study is to evaluate the effect of type of the tooth and the placement site of electrode on electrical pulp testing of the anterior teeth. Twenty persons were participated in this study. The six maxillary and mandibular anterior teeth were checked to evaluate the response threshold to electrical pulp testing; each tooth was examined at four placement sites on its labial surface, which are the incisal edge, incisal third, middle third and the cervical third. The results showed that the response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…Threshold levels in this study support these statements, as they were lowest at the incisal edges of the incisors for both the fluorotic and non‐fluorotic teeth, and highest at the cervical third. Similar findings have been reported for the anterior teeth in other studies (6,9,10,21) while Jacobson (7) in an in vitro study reported that the middle third electrode placement sites of the labial surface of maxillary incisors had the least resistance.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Threshold levels in this study support these statements, as they were lowest at the incisal edges of the incisors for both the fluorotic and non‐fluorotic teeth, and highest at the cervical third. Similar findings have been reported for the anterior teeth in other studies (6,9,10,21) while Jacobson (7) in an in vitro study reported that the middle third electrode placement sites of the labial surface of maxillary incisors had the least resistance.…”
Section: Discussionsupporting
confidence: 88%
“…There is, however, no consensus on this. Like several others (6,9,10,21), the current study employed the maxillary central incisors. The choice was based on their location and ease of access, reduced incisal edge wear unlike what can be commonly seen with the posterior teeth and the pulp size reduction that follows secondary dentin deposition.…”
Section: Discussionmentioning
confidence: 99%
“…These claims are supportive of the threshold values found in this investigation, which were highest at the cervical third and lowest at the incisal margins of the incisors for both fluorotic and non-fluorotic teeth. Other studies have revealed similar results for the anterior teeth 15,28 . An in vitro study by Jacobson et al only demonstrated the middle third of the labial surface of maxillary incisor teeth to be the site for lowest threshold readings 29 .…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, in both fluorosed and nonfluorosed teeth incisal edge showed lowest threshold levels for EPT when compared to incisal, middle and cervical thirds because the enamel is thinnest incisally with the highest concentration of neural elements in the pulp horns while in the cervical area the number of nerve fibers decrease. [ 31 ] The straight course of dentinal tubules at the incisal edges of anterior teeth offers faster flow rate to the electric current. [ 12 ] This explains why the threshold values were lower at the incisal edge region than in the cervical third.…”
Section: Discussionmentioning
confidence: 99%